Gastrointestinal parasites found in a green iguana (iguana iguana) - Özlem Derinbay Ekici; Nermin Isik; Feyzullah Guclu (Eurasian Journal of Veterinary Sciences)
This case report reported that nematode and cestod eggs found in the digestive system of a green iguana (iguana iguana). A 9 month-old green iguana (iguana iguana) weighing 95 g was presented by its owner for physical examination to parasitology laboratory. The owner said that nutritional condition was poor. The nematode [Oxyuris spp.) and ces-tode [Mesocestoides spp.) eggs were diagnosed by fecal flotation and the animal was treated with ivermectin [0.2 mg/kg, PO) plus praziquantel [10 mg/kg, SC) in two weeks apart. The last fecal examination was negative. After treatment, owner of the iguana said that iguana had a normal appetite and well appearance.